Combination of SCOR-BSC and Regression Linear Programming to Assess the Performance of Construction SMEs in DIY and Central Java - Harsoyo, Yoga Aprianto; Wibowo, Mochamad Agung; Hatmoko, Jati Utomo Dwi; Fitria, Hanin (International Journal of Integrated Engineering, 2023)
Several metrics in the supply chain performance assessment system cannot be uncovered by merely putting a strategy into action. Meanwhile, the balanced scorecard strategy necessitates the incorporation of numerous measures derived from the implementation of strategies, ultimately guiding the business toward its long-term orientation. The same is true for evaluating the effectiveness of a supply chain. The Business Service Chain (BSC) takes three viewpoints of the Supply Chain Operations Reference (SCOR) and expands them into four: financial, customer, internal business, and innovation and learning. Both the SCOR and BSC methods can be utilized to implement a sustainable supply chain management system. These two methods were employed to solve supply chain issues in the construction industry. BSC aimed to compensate for SCOR’s limited focus on performance by considering two angles—those of internal business operations and customers. When compared to SCOR, BSC’s uniformity in the supply chain allowed for more adaptable metrics when resizing; more applicable models, encompassing all processes; and easier performance monitoring; all through the utilization of various metrics.